Root Pruning of Strawberry Transplants - John R. Duval; Elizabeth Golden (EDIS, 2003)
This is document HS-913, one of a series of the Horticultural Sciences Department, Gulf Coast Research and Education Center - Bradenton, Florida. Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2003.